1992
DOI: 10.1093/tropej/38.6.314
|View full text |Cite
|
Sign up to set email alerts
|

A Community-based Study of Childhood Handicap in Oman

Abstract: This paper reports the findings of a preliminary survey carried out in an Omani community to assess the prevalence of handicap amongst children, and its impact on the family. The sample comprised of 492 children less than 15 years of age. The disabilities identified related to chromosomal abnormality, genetic, perinatal, and infectious factors. The presence of mental retardation, with associated social taboos, confounds the problem in Oman. The study showed that, although some handicapped children may be accep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The regional distribution of SCD revealed that it was more prevalent (more than 70% of cases) in regions with smear-positive rates of malaria of 1 to >5 per cent (parts of Dhahira, Dakhliya, North and South Shargiya). Al-Riyami et al 55 reported the overall prevalence of HbS as 5.8 per cent, though there were significant regional variations. Clinical variations in SCA presentation are largely related to the presence of different β-globin gene haplotypes identified during molecular studies, where Benin, Bantu and Saudi-Indian haplotypes were shown to be present in Oman 52 56 .…”
Section: Frequency and Distribution Of Sickle Cell Gene Among Arabsmentioning
confidence: 98%
“…The regional distribution of SCD revealed that it was more prevalent (more than 70% of cases) in regions with smear-positive rates of malaria of 1 to >5 per cent (parts of Dhahira, Dakhliya, North and South Shargiya). Al-Riyami et al 55 reported the overall prevalence of HbS as 5.8 per cent, though there were significant regional variations. Clinical variations in SCA presentation are largely related to the presence of different β-globin gene haplotypes identified during molecular studies, where Benin, Bantu and Saudi-Indian haplotypes were shown to be present in Oman 52 56 .…”
Section: Frequency and Distribution Of Sickle Cell Gene Among Arabsmentioning
confidence: 98%